SURGICAL MANAGEMENT OF AURAL HEMATOMA IN A RABBIT - Malik Abu Rafee; Anwar Hassan; Santi Jaya Lekshmi; Amarpal (Exploratory Animal and Medical Research, 2017)
A one year old male rabbit was presented with a history of hanging swollen left ear since a week. It was diagnosed as aural hematoma and surgical drainage of the haematoma under general anaesthesia was considered. Animal recovered uneventfully.